THE ROLE OF SCIENCE, EDUCATION AND PRODUCTION INTEGRATION IN THE TRAINING OF PERSONNEL FOR CONSTRUCTION EDUCATIONAL AREAS - Akhmedov Islombek; Kholmirzayev Sattor; Umarov Isroil (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This scientific article outlines methods for implementing science taste and production integration to further improve the quality of education in construction education areas. The work carried out by the professors and teachers of the department and their results are covered in this direction.